Relapsing Fevers: Neglected Tick-Borne Diseases - Talagrand-Reboul, Emilie; Boyer, Pierre H.; Bergström, Sven; Vial, Laurence; Boulanger, Nathalie (Frontiers in Cellular and Infection Microbiology, 2018)
Relapsing fever still remains a neglected disease and little is known on its reservoir, tick vector and physiopathology in the vertebrate host. The disease occurs in temperate as well as tropical countries. Relapsing fever borreliae are spirochaetes, members of the Borreliaceae family which also contain Lyme disease spirochaetes. They are mainly transmitted by Ornithodoros soft ticks, but some species are vectored by ixodid ticks. Traditionally a Borrelia species is associated with a specific vector in a particular geographical area. However, new species are regularly described, and taxonomical uncertainties deserve further investigations to better understand Borrelia vector/host adaptation. The medical importance of Borrelia miyamotoi, transmitted by Ixodes spp., has recently spawned new interest in this bacterial group. In this review, recent data on tick-host-pathogen interactions for tick-borne relapsing fevers is presented, with special focus on B. miyamotoi.